2007
DOI: 10.1097/01.pgp.0000229994.02815.f9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Extracellular Matrix Proteins in Ovarian Serous Tumors

Abstract: The aims of this study were to perform a comprehensive expression analysis of the genes encoding extracellular matrix proteins and to investigate the expression pattern in one of these proteins, syndecan 1, in normal ovarian epithelium as well as benign and malignant ovarian serous tumors. Gene expression of 16 different extracellular matrix proteins was analyzed in ovarian serous tumors based on serial analysis of gene expression database. Semiquantitative reverse transcription-polymerase chain reaction was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
(4 reference statements)
0
17
0
4
Order By: Relevance
“…This would be expected of an ECM protein. In addition, a number of proteomic and microarray studies of human tissues (Table 1) have identified EMILIN2 in extracellular fluids (plasma, synovial, amniotic and seminal plasma), stem cells (hematopoietic, mesenchymal, osteoblasts), stimulated endometrial stromal cells, cancer cells (hepatic, lymphocytic leukemia, colorectal cancer, and ovarian cancer), and as a cell surface marker for human embryonic stem cell-derived cardiomyocytes [36-50]. A recent study [40] reported down-regulation of EMILIN2 in brain arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…This would be expected of an ECM protein. In addition, a number of proteomic and microarray studies of human tissues (Table 1) have identified EMILIN2 in extracellular fluids (plasma, synovial, amniotic and seminal plasma), stem cells (hematopoietic, mesenchymal, osteoblasts), stimulated endometrial stromal cells, cancer cells (hepatic, lymphocytic leukemia, colorectal cancer, and ovarian cancer), and as a cell surface marker for human embryonic stem cell-derived cardiomyocytes [36-50]. A recent study [40] reported down-regulation of EMILIN2 in brain arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are known to interfere with the normal programming of ECM biosynthesis and can extensively modify the structure and composition of the matrix [6]. Alterations in the extracellular environment are critical for tumor initiation and progression and intra-peritoneal dissemination [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis seems not to be supported by two different studies of gene expression and proteomic analysis related to matrix protein profiles in ovarian carcinomas and soft tissue osteosarcomas where EMILIN1 was upregulated [142,143]. A pro-or anti-tumor action could be exerted by EMILIN1 in a tissue-specific manner.…”
Section: Emilin1 and Cancermentioning
confidence: 90%